Influence of double-sided delta-wing tape insert with alternate-axes on flow and heat transfer characteristics in a heat exchanger tube - Eiamsa-ard, Smith; Promvonge, Pongjet (My University, 2011)
The convective heat transfer and friction behaviors of turbulent tube flow through a straight tape with double-sided delta wings (T-W) have been studied experimentally. In the current work, the T-W formed on the tape was used as vortex generators for enhancing the heat transfer coefficient by breakdown of thermal boundary layer and by mixing of fluid flow in tubes. The T-W characteristics are (1) T-W with forward/backward-wing arrangement, (2) T-W with alternate axis (T-WA), (3) three wing-width ratios and (4) wing-pitch ratios. The experimental result reveals that for using the T-W, the increases in the mean Nusselt number (Nu) and friction factor are, respectively, up to 165% and 14.8 times of the plain tube and the maximum thermal performance factor is 1.19. It is also obvious that the T-W with forward-wing gives higher heat transfer rate than one with backward-wing around 7%. The present investigation also shows that the heat transfer rate and friction factor obtained from the T-WA is higher than that from the T-W. In addition, the flow pattern and temperature fields in the T-W tube with both backward and forward wings were also examined numerically.
Keywords: Alternate axis; Fluid flow; Heat transfer; Tape with centre-wing; Vortex; Wing